Work from Home Challenges Faced by Private Sector Employees During Pandemic COVID-19: A Case of ‘A’ Property Company in Johor - Periasamy Nathan, Lalitha; Omar, Siti Sarah; Mohd Angsor, Mohd Asmadi (Research in Management of Technology and Business, 2021)
Due to the spread of Covid-19 virus, public and private sectors had to implement work from home policy to carry out their jobs. Employees faced challenges during work from home policy and affect the employee performance. Therefore, the purpose of this study is to explore the challenges faced by employees during the Covid-19 outbreak’s work from home period, as well as the impact of such challenges on employee performance. This study employs qualitative methodology by interviewing seven purposive sample of respondents from ‘A’ Property Management Sdn Bhd private company in Johor Malaysia. The thematic analysis was used to analyze data. Research findings show that the most significant challenge respondents faced while working remotely was technological. A lack of knowledge on how to handle the virtual platforms and internet disruptions has a negative impact on respondents’ work performance. This study is important to expand the knowledge of work from home challenges and their effect on employees’ performance. Besides, it provides managerial implications to the company on how the managers would improve the work from home policy so that employees would still performing their very best at home.